Peninjauan Kembali Determinan Pembelian Minuman Sehat di Kalangan Konsumen Muda Indonesia - Clara, Catharina; Angel, Alycia (Jurnal Manajemen Indonesia, 2025)
This study investigates the influence of ethical marketing, social environment, and health consciousness on consumers’ purchasing decisions of beverages claimed to be “healthy.” Employing a quantitative approach with a purposive sample of 193 respondents, data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4. The findings show that social environment and health consciousness significantly influence purchase decisions, while ethical marketing does not have a direct impact. Furthermore, health consciousness does not moderate the relationship between ethical marketing or social environment and purchasing decisions. These results suggest that consumers are more strongly influenced by social factors and personal health awareness than by ethical marketing messages alone. The study’s contribution lies in its integrated model, which examines the combined and interactive effects of these variables—offering a more comprehensive understanding of consumer behavior in the growing health beverage sector. While previous research has considered these factors separately, this study highlights the relative strength of social and health-driven motivations and reveals the limited moderating role of health consciousness—an area often overlooked in existing literature. Practically, marketers should prioritize strategies that leverage peer influence and social media engagement while communicating clear health benefits to enhance brand appeal. Ethical marketing efforts may be more effective when embedded within socially resonant and health-oriented narratives. For policymakers, these findings underscore the importance of promoting public health awareness and ensuring transparent marketing practices. Overall, the study offers new insights relevant to both academic and industry efforts aimed at encouraging responsible and health-conscious consumer behavior.